Analisis Gaya Bahasa dan Majas Pada Lagu “Raksa” Karya Soegi Bornean - Reinaldo, Christopher; Muhammad Taufik (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This article explores the richness of language styles and speech used in the lyrics of the song "Raksa" by Soegi Bornean. Against the background of the richness of the existing lyrics and the possibilities that exist in linguistic exploration as found in the title of the song "Raksa" which comes from a foreign language, namely Sanskrit, as well as the use of the song lyrics "Budaya nian bersua", and the aim of this research is to reveal The contribution of songs to the development of diction in song lyrics is due to the large number of vocabulary words in Indonesian that are rarely used. As well as the emotional power of using qualitative descriptive analysis methods to study the language style and figures of speech of the Raksa Song, this research will focus on deciphering the stylistic nuances and revealing the mosaic of metaphorical and idiomatic expressions. The research results further highlight the complexity of the rhetorical figures of speech contained in the song "Raksa" such as in the lyrics which read "Where I look for the soul" of the song, providing insight into its poetic resonance. Therefore, the use of language styles and figures of speech has spread to a deeper scale regarding song lyrics, and has enriched the appreciation of Indonesian songwriting.